Scales of Captivity - Brady, Mary Pat (Duke University Press, 2022)
Mary Pat Brady traces the figure of the captive and cast-off child over 150 years of Latinx/Chicanx literature as a critique of colonial modernity and the forms of confinement that underpin racialized citizenship.